Teaching English Writing Skill for: Academic Writing and Free/Creative Writing For Student - Fitrah Yuliawati; Ika Nuriyanti (Universitas Islam Madura, 2019)
English is the more powerfull language around the world it can be seen around the world many people knowing and using English well. There are so many languages likes Indonesian, Spanish, Chiness, France, etc. But English always using as communication between other people around this world. Using English it means knowing better how to speak, read, listen and write about it. The difficult one of express about English is that how to writing down English language. Like another language in this word, English has it owns rule and grammar to write. And writing English can be divided into two kinds such as academical writing and free writing. From these kind of writing, the difference between both of them is also clear when practicing English writing, because writing is never a one-step action; it is an ongoing creative act. When you first write something, you have already been thinking about whta to say and how to say it. Then after you have finished writing, you read over what you have written and make changes and corrections. You write and revise and write and revise again until you are satisfied that your writing express exactly what you want to say.